Digital daydreaming: Introducing the spontaneous smartphone checking scale. Issue 1 (10th January 2023) - Berntsen, Dorthe; Hoyle, Rick H.; Munkholm Møller, Daniel; Rubin, David C.
Abstract: Smartphones are a ubiquitous part of many people's lives, but little is known about their impact on everyday thought processes. Here we introduce the spontaneous smartphone checking scale (SSCS)—which measures the tendency to direct attention toward one's smartphone, unpreceded by external prompts (e.g., notifications, or alerts) and with no specific conscious goal in mind, as a parallel to mind‐wandering directed toward internal thoughts. The SSCS showed good psychometric properties and construct validity. It separated from measures of daydreaming and mind‐wandering by not loading on dimensions related to self‐consciousness, reflection, and rumination, but instead loading highly on a factor associated with other aspects of digital communication and concerns about public appearance on social media. This suggests that spontaneous smartphone checking serves different mental and social functions than internally generated spontaneous thought processes. We discuss possible long‐term effects of spontaneous smartphone checking taking up time for internally generated spontaneous thoughts.